Konflik Sosio-Religius Jemaat Korintus: Sebuah Investigasi tentang Kesimpangsiuran Makna Karunia Rohani - Siagian, Handra (Sekolah Tinggi Teologi Baptis, Jakarta, 2024)
The Apostle Paul is a crucial figure in the New Testament who played a significant role in the early development of Christianity, particularly among non-Jews. He established congregations in various cities such as Corinth, Galatia, Ephesus, Philippi, and Thessalonica, successfully crossing ethnic, cultural, and religious boundaries. However, the presence of co-workers like Apollos, Cephas, and James often caused divisions among the congregations. These divisions were influenced by the immaturity of the believers' faith and the socio-economic differences within the Corinthian society, leading them to idolize certain preachers rather than focusing on the core message of the Gospel. The confusion over understanding spiritual gifts further complicated the conflicts within the Corinthian church. Paul emphasized that spiritual gifts are meant to unite and strengthen the congregation's faith, equip them with power, and build up the body of Christ. Through his letters, Paul sought to reaffirm the principles of God's Word and address the divisions, aiming to create a harmonious and strong-faith congregation in Christ. This research employs a qualitative approach with historical analysis and exegesis of biblical texts, along with contextual analysis of the social, economic, and cultural conditions of Corinthian society in the first century AD. The findings indicate that the socio-religious conflicts within the Corinthian church can be resolved by understanding the meaning of spiritual gifts and applying appropriate solutions to foster harmony in congregational life. AbstrakRasul Paulus merupakan tokoh kunci dalam Perjanjian Baru yang berperan besar dalam perkembangan awal Kekristenan, terutama di kalangan non-Yahudi. Ia mendirikan jemaat di berbagai kota seperti Korintus, Galatia, Efesus, Filipi, dan Tesalonika, dan berhasil melintasi batas suku, budaya, dan agama. Namun, kehadiran saudara sepelayanan seperti Apolos, Kefas, dan Yakobus sering menyebabkan perpecahan di antara jemaat. Perpecahan ini dipengaruhi oleh ketidakdewasaan iman jemaat dan perbedaan sosial-ekonomi masyarakat Korintus, yang lebih mengidolakan pelayan tertentu daripada fokus pada inti Injil. Kesimpangsiuran pemahaman tentang karunia rohani menambah kompleksitas konflik di jemaat Korintus. Paulus menekankan bahwa karunia rohani bertujuan untuk mempersatukan dan memperkuat iman jemaat, memperlengkapi mereka dengan kuasa, dan membangun tubuh Kristus. Melalui surat-suratnya, Paulus berusaha menegaskan prinsip-prinsip kebenaran Firman Tuhan dan mengatasi perpecahan, dengan harapan menciptakan jemaat yang harmonis dan beriman kuat dalam Kristus. Penelitian ini menggunakan metode kualitatif dengan analisis historis dan analisis kontekstual terhadap kondisi sosial, ekonomi, dan budaya masyarakat Korintus pada abad pertama Masehi. Hasil penelitian menunjukkan bahwa konflik sosio-religius di jemaat Korintus dapat diatasi dengan memahami makna karunia rohani dan menerapkan solusi yang sesuai untuk menciptakan keharmonisan dalam kehidupan berjemaat.